2019
DOI: 10.1111/den.13548
|View full text |Cite
|
Sign up to set email alerts
|

Combination of bisacodyl suppository and 1 L polyethylene glycol plus ascorbic acid is a non‐inferior and comfortable regimen compared to 2 L polyethylene glycol plus ascorbic acid

Abstract: Background and Aim: Appropriate bowel cleansing before colonoscopy is an important factor in increasing the detection rate of lesions. Low-volume polyethylene glycol (PEG) plus ascorbic acid (PEG-Asc) reduces the dosage of bowel preparation agent, but still presents discomfort to patients. The primary aim of the present study was to compare the efficacy of bowel cleansing between 2 L PEG-Asc (control) and 1 L PEG-Asc with bisacodyl suppository (suppository) groups, and the secondary aim was to investigate comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…The results of this study showed no statistical differences, while only a conservative estimation can be done due to limited sample size in this part. Based on the current available literature, our results supported the use of additional adjuvants solely with PEG-Asc solution [17][18][19][20][21]. According to a hypothesis, the cathartic effect of bisacodyl and prucalopride might be due to its cathartic or prokinetic mechanism, which in turn changes the motor patterns in the colon and promotes the intestinal movement [31,32].…”
Section: Biomed Research Internationalsupporting
confidence: 70%
See 3 more Smart Citations
“…The results of this study showed no statistical differences, while only a conservative estimation can be done due to limited sample size in this part. Based on the current available literature, our results supported the use of additional adjuvants solely with PEG-Asc solution [17][18][19][20][21]. According to a hypothesis, the cathartic effect of bisacodyl and prucalopride might be due to its cathartic or prokinetic mechanism, which in turn changes the motor patterns in the colon and promotes the intestinal movement [31,32].…”
Section: Biomed Research Internationalsupporting
confidence: 70%
“…Almost all the studies included in this meta-analysis were internally consistent in these respects in order to eliminate the influence of these confounding factors on the results. Nevertheless, in Kim's trial, a statistically significant difference was observed in the mean age of patients [20]. Our study results showed that patients in the 2L group (48.14 vs. 52.88) were younger, which was under the common cut-off, and the results ultimately showed no significant difference between the two groups [22].…”
Section: Biomed Research Internationalmentioning
confidence: 47%
See 2 more Smart Citations
“…23 Furthermore, the protein ASC is also associated with cancer cell death. 24 Based on these findings, some scientists have paid attention on regulatory effect of ASC on drug intervention in cell pyroptosis. In addition, Miyata et al found that upregulation of ASC could significantly inhibit the progression of cancer.…”
Section: Discussionmentioning
confidence: 99%